Italy between a disaster and a new development strategy - Francesco Pastore (Institute of Labor Economics (IZA), 2020)
Italy has probably been one of the first ships to cross the storm of the pandemic, soon after Wuhan in China, and one of the worst performers with a GDP fall of -10% in 2020. The reason is that the pandemic recession has drawn on old structural problems, which already before the pandemic made the country one of the worst performers in terms of growth rates in Europe in the last 20 years. The evils of Italy are well known. It is the second biggest manufacturer in Europe, but also among the most traditional ones. Made in Italy, despite moving up in terms of quality and skilled content, still remains the most exposed to the competition from emerging market economies. The crisis was already ongoing when Italy joined the euro currency, and the strong currency made things worse. The necessary industrial upgrading from traditional manufacturing to the new branches of industry would have required strong public investment in infrastructure, which were not allowed or not possible due to the Maastricht Treaty of 1993, the economic and financial crisis at the end of the 2000s, and the Fiscal compact of 2012. The pandemic has changed the mind of the European Union (EU) governance. Strangely enough, the virus yielded a common destiny to all the EU member states as never before, also in financial matters. This eventually led to the implementation of the so-called Recovery Fund (RF) or Next Generation Fund (NGF). Italy should use the 209 billion euros of the Fund to bring the country not only out of the pandemic storm, but also out of the euro currency storm. For the first time, after decades in which the EU Troika was conveying only sad messages, the EU is all over Europe seen as hope for hundreds of millions of people.
Keywords: F45; F69; J28; O52; 330; COVID-19; emergency; pandemic recession; high road todevelopment; Next Generation Fund; Italy